Localization of ictal pouting in frontal lobe epilepsy: A case report - Koc, Guray; Bek, Semai; Gokcil, Zeki (Elsevier Science Inc, 2017)
[Abstract Not Available]
Keywords: Gendarme; Chapeau; Sign; Seizures